Denmark : 2021 Article IV Consultation-Press Release; Staff Report; and Staff Supplement. (IMF Staff Country Reports; Country Report ;, 2021)
Denmark entered the pandemic on a strong economic footing and utilized its large policy space built over time to successfully address the crisis and lay the ground for a strong recovery. The outlook is for a rebound in activity, but uncertainty remains elevated with risks tilted to the downside. Macrofinancial vulnerabilities persist as housing price growth has accelerated and household debt remains high. The current account declined but remains in surplus.